Learning about research and readership development in STEM education: a systematic analysis of the journal's publications from 2014 to 2018 - Yeping Li; Jeffrey E. Froyd; Ke Wang (SpringerOpen, 2019)
Abstract In this editorial, we conduct a systematic review of 144 items published in the International Journal of STEM Education over its first 5-year period from 2014 to 2018. We analyze publication quantities and types, authorship nationality, publication readership, research topic, and top 10 most accessed and top 10 most cited articles over the years. The results provide a snapshot of the research and readership development in multidisciplinary STEM education as an international field.